The experience of living with patellofemoral pain: loss, confusion and fear-avoidance: a UK qualitative study - Smith, Benjamin E.; Moffatt, Fiona; Hendrick, Paul; Bateman, Marcus; Rathleff, Michael Skovdal; Selfe, James; Smith, Toby O.; Logan, Pip (BMJ Publishing Group Ltd, 2018)
Objectives: To investigate the experience of living with patellofemoral pain.